UTILIZATION OF ISOFLAVONES WITH BASIC MATERIAL OF ROBUSTA COFFEE SKIN WITH BMD (BONE MARROW DENSITY) MARKERS IN PERI / POST MENOPAUSAL WOMEN - Puspita Sari, Ratna Dewi; Bakrie, Samsul (Biomedical Journal of Indonesia, 2019)
The increase in life expectancy of women in Indonesia, which reaches 72 years of age causes almost a third of her life span lived at the time of menopause. The population of menopausal women in Indonesia will increase with all the effects due to decreased estrogen in the form of climatic complaints and an increased risk of bone loss / osteoporosis. The best choice and is the standard treatment for climatic complaints and osteoporosis is hormonal therapy (Estrogen + Progesterone / Estrogen). WHI in 2004 stated that hormone therapy in menopausal women increases the risk of breast cancer. In Indonesia, phytoestrogens are widely circulated in the market with the category of supplements and have been used by the public to deal with climatic complaints and osteoporosis. This phytoestrogen has not been scientifically proven to be useful for overcoming climatic and osteoporotic complaints in postmenopausal women. Phytoestrogens on the market used as Permi III pills contain Red Clover, Black Cohosh and calcium. Some studies say that phytoestrogens for osteoporosis therapy can be obtained from isoflavones derived from robusta coffee skins. This isoflavone can affect bone mineral density in peri / postmenopausal women. The use of phytoestrogens (isoflavones) from the skin of coffee beans affects peri / postmenopausal women and helps maintain and build bone mass (reduce the occurrence of osteoporosis complaints).